Developing a sustainable food strategy for large organizations: The importance of context in shaping procurement and consumption practices. (8th February 2018) - Goggins, Gary
Abstract: Organizations such as hospitals, educational institutions and workplaces feed thousands of people every day and are key intermediaries in the food system. They are in a position to significantly shape the production, processing and distribution of food as well as food‐related practices of large groups. These activities have a significant impact on sustainable development, the global economy and health and wellbeing. Using a qualitative approach that draws on 21 interviews with key decision‐makers based in eight large national and multinational organizations, this research examines the most important contextual factors that influence food provisioning across organizations. The study identifies opportunities and constraints for improving food sustainability that are likely to apply within and across different organizational contexts, and provides recommendations for implementing a sustainable food strategy. The findings provide interesting theoretical insights and have practical implications that are relevant for practitioners, business managers and sustainability consultants.